PENGARUH GAYA KEPEMIMPINAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA ( Studi Pegawai Politeknik Ilmu Pelayaran Semarang ) - Santiko, Tony (Students Journal of Accounting and Banking, 2012)
Target of this research to test work characteristic influence and discipline to organizational commitment with in mediation by satisfaction work officer in Politeknik Ilmu Pelayaran Semarang. Pursuant to the mentioned hence this research take title âPengaruh Gaya KepemimpinanÂ  Dan Karakteristik Pekerjaan Terhadap Kinerja Pegawai Dengan Mediasi Kepuasan Kerja (Studi Pegawai Politeknik Ilmu Pelayaran Semarang )â. In this research take Politeknik Ilmu Pelayaran Semarang Officer amounting to 218 people. Intake of Sample with sampling purposive technique representing method intake of sample by determining criterion beforehand that is officer having minimum year of service three year. As for sample which is taken in this research equal to 100 responder. Data analysis use doubled linear regression. Pursuant to result of research which have been done by hence can know by leadership style and work characteristic have an effect on to satisfaction of job. Leadership style, work characteristic and satisfaction of job have an effect on to officer performance. For the test of satisfaction mediation work leadership style influence mediation and work characteristic to officer performance. Â  Keyword : Style leadership, work characteristic, satisfaction work and officerÂ  performance